2017
DOI: 10.3390/molecules22081374
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Toxicological Screening of Novel Benzimidazole-Morpholine Derivatives as Dual-Acting Inhibitors

Abstract: The aim of this study was to investigate acetylcholinesterase (AChE), monoamine oxidase A (MAO-A), monoamine oxidase B (MAO-B), cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) enzyme inhibitory, and antimicrobial activities of a new series of 2-(4-substituted phenyl)-1-[2-(morpholin-4-yl)ethyl]-1H-benzimidazole derivatives, for their possible use as multi-action therapeutic agents. Target compounds (n = 15) were synthesized under microwave irradiation conditions in two steps, and their structures were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…The results of the present study did not show any significant increases in the frequencies of SCEs and MN in lymphocytes after exposure to all synthesized compounds as compared to the control values in all three dose treatments ( Table 2). The toxicological screening of novel benzimidazole-morpholine derivatives performed by Ames test showed that the synthesized compounds had no genotoxic effects, in accordance with our findings [32]. In contrast to our results, the previous studies conducted by in vitro cytochalasin-B micronucleus test on human lymphocytes revealed that thiabendazole, carbendazim, and mebendazole containing benzimidazole rings caused an increase in MN frequency in a dose-dependent manner [33].…”
Section: Resultssupporting
confidence: 90%
“…The results of the present study did not show any significant increases in the frequencies of SCEs and MN in lymphocytes after exposure to all synthesized compounds as compared to the control values in all three dose treatments ( Table 2). The toxicological screening of novel benzimidazole-morpholine derivatives performed by Ames test showed that the synthesized compounds had no genotoxic effects, in accordance with our findings [32]. In contrast to our results, the previous studies conducted by in vitro cytochalasin-B micronucleus test on human lymphocytes revealed that thiabendazole, carbendazim, and mebendazole containing benzimidazole rings caused an increase in MN frequency in a dose-dependent manner [33].…”
Section: Resultssupporting
confidence: 90%
“…Each experiment in antifungal assay was performed twice. The details of the anticandidal assay were reported in our previous study [55].…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro antifungal activities of all resynthesized derivatives 4a-4o were screened at between 1 mg/mL-1.95 µg/mL concentrations using various Candida strains including C. albicans (ATCC 90030), C. glabrata (ATCC 90030) C. krusei (ATCC 6258) and C. parapsilopsis (ATCC 22019) and following the protocol of the EUCAST in keeping with the previous studies reported by our research group [21,22].…”
Section: Antifungal Activitymentioning
confidence: 99%
“…According to the protocol of the EUCAST reported previously by our research group [21,22], all obtained compounds 4a-4o were screened for their in vitro antifungal activity against four pathogenic fungi;…”
Section: Antifungal Activitymentioning
confidence: 99%